Characterization of intestinal mononuclear phagocyte subsets in young ruminants at homeostasis and during Cryptosporidium parvum infection - Baillou, Ambre; Tomal, Florian; Chaumeil, Thierry; Barc, Céline; Levern, Yves; Sausset, Alix; Pezier, Tiffany; Schulthess, Julie; Peltier-Pain, Pauline; Laurent, Fabrice; Lacroix-Lamandé, Sonia (Frontiers in Immunology, 2024)
Cryptosporidiosis is a poorly controlled zoonosis caused by an intestinal parasite, Cryptosporidium parvum (C. parvum), with a high prevalence in livestock (cattle, sheep, goats). Young animals are particularly susceptible to this infection due to the immaturity of their intestinal immune system. In a neonatal mouse model, we previously demonstrated the importance of the innate immunity and in particular of type 1 conventional dendritic cells (cDC1) among mononuclear phagocytes (MP) in controlling the acute phase of C. parvum infection. These immune populations are well described in mice and humans, but their fine characterization in the intestine of young ruminants remained to be further explored. Here, we identified one population of macrophages and three subsets of cDC (cDC1, cDC2 and a minor cDC subset with migratory properties) in the intestine of lamb and calf by phenotypic and targeted gene expression analyses. Unsupervised single cell transcriptomic analysis confirmed the identification of these 4 intestinal MP subpopulations in lamb, while highlighting a deeper diversity of cell subsets among monocytic and dendritic cells. We demonstrated a weak proportion of cDC1 in the intestine of newborn lambs that are highly susceptible to C. parvum infection, together with an increase of these cells in response to the infection, assuming their importance for efficient parasite control as in the mouse model. In this study, we established the first fine characterization of intestinal MP subsets in young lambs and calves providing new insights for comparative immunology of the intestinal MP system across species and for future investigations on host-Cryptosporidium interactions in target species.